The global economy and the euro area: Increased uncertainty is dampening growth - Ferdinand Fichtner; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Weekly Report, 2018)
The political conditions for growth are currently dominated by increased uncertainty; this is particularly weighing on investment activity and slowing down the global economy. DIW Berlin is lowering its forecast slightly for this year and the next to 4.1 percent and 3.9 percent, respectively. However, global expansion appears to remain intact. In developed economies, primarily the good labor market situation is supporting consumption. In the United States, higher growth than at the beginning of the year is expected due to fiscal stimulus. The outlook for the euro area has deteriorated recently, however. Many emerging countries are also under greater pressure-in addition to domestic issues mainly caused by a tightening of international financial conditions. Over the course of the rest of the year, the rise in global interest rates, the first labor shortages in developed economies, and a further gradual deceleration of growth in China are expected to slow down the global economy more. The main risks for the continuation of the global upswing are primarily the United States' protectionism and political uncertainties in the euro area.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook